Green Tax in Various Countries: A Review of Implementation and its Relevance for Indonesia - Ana Ni’matul Laila; Heru Tjaraka (Eduvest - Journal of Universal Studies, 2026)
Climate change and environmental degradation have become critical global issues, driving the emergence of green tax policies as a key fiscal instrument. This study reviewed the implementation of environmental taxation, especially carbon tax, in several countries including Sweden, Canada (British Columbia), Spain, and Malaysia. Through a qualitative literature review approach, it examined the effectiveness, policy design, and socio-political acceptance of green tax initiatives in different contexts. These findings highlight that successful implementation depends not only on tax structures but also on public legitimacy, revenue recycling mechanisms, and integration with broader economic and environmental strategies. Drawing lessons from this international experience, this study evaluates the potential and challenges of implementing green tax policies in Indonesia. The report concludes that with careful policy design, institutional readiness, and public engagement, green taxes can serve as a strategic tool to support sustainable development and fiscal reform in Indonesia. The results of this study have two main implications. First, in terms of policy, this study provides concrete recommendations for the Indonesian government in designing an adaptive carbon tax scheme, especially regarding the importance of pro-people revenue recycling mechanisms and the transparency of the use of tax funds to build public legitimacy. Second, practically, this research implies the need to strengthen institutional capacity and cross-sector coordination before the carbon tax is fully implemented, as well as the need for effective public communication strategies to reduce socio-political resistance